L-3-n-Butylphthalide Protects HSPB8 K141N Mutation-Induced Oxidative Stress by Modulating the Mitochondrial Apoptotic and Nrf2 Pathways - Yang, Xiao-Dong; Cen, Zhi-Dong; Cheng, Hai-Peng; Shi, Kai; Bai, Jie; Xie, Fei; Wu, Hong-Wei; Li, Bei-Bei; Luo, Wei (Frontiers in Neuroscience, 2017)
Charcot–Marie–Tooth disease (CMT), also known as hereditary motor and sensory neuropathy, is the most common inherited peripheral nerve disorder. Missense mutations, such as K141N, in the small heat shock protein HSPB8 are known to cause distal hereditary motor neuropathy 2A (dHMN2A) or Charcot-Marie-Tooth neuropathy type 2L (CMT2L). However, of critical clinical significance, very few specific therapies for this disease exist. In the present study, we investigated the impact of mutant K141N HSPB8 on mitochondrial distribution and function in a cellular model of CMT2L. Our results indicate that K141N HSPB8 induced mitochondrial aggregation and caused increased oxidative stress injury. As an extraction from Chinese celery Apium graveolens Linn seeds, L-3-n-Butylphthalide (NBP), has been reported to exert many neuroprotective effects, we interrogated whether NBP could elicit a protective effect on the cell injury typically caused by HSPB8 K141N mutations. We found NBP could reverse the pathological processes induced by HSPB8 K141N mutation via an antioxidant effect, modulation of the Bax/Bcl-2 mitochondrial apoptotic and Nrf2 pathways. We propose a novel function of HSPB8, highlighting the consequence of the K141N pathogenic mutation. Furthermore, we suggest NBP may have promising therapeutic potential in the treatment of CMT2L.